Tipburn in salt-affected lettuce (Lactuca sativa L.) plants results from local oxidative stress - Carassay, Luciano Raul (2012)
Tipburn in lettuce is a physiological disorder expressed as a necrosis in the margins of young developing leaves and is commonly observed under saline conditions. Tipburn is usually attributed to Ca 2+ deficiencies, and there has very limited research on other mechanisms that may contribute to tipburn development. This work examines whether symptoms are mediated by increased reactive oxygen species (ROS) production.Two butter lettuce (Lactuca sativa L.) varieties, Sunstar (Su) and Pontina (Po), with contrasting tipburn susceptibility were grown in hydroponics with low Ca 2+ (0.5mM), and with or without 50mM NaCl. Tipburn symptoms were observed only in Su, and only in the saline treatment. Tipburn incidence in response to topical treatments with Ca 2+ scavengers, Ca 2+ transport inhibitors, and antioxidants was assessed. All treatments were applied before symptom expression, and evaluated later, when symptoms were expected to occur. Superoxide presence in tissues was determined with nitro blue tetrazolium (NBT) and oxidative damage as malondialdehyde (MDA) content. Superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) activities were assayed.Under control and saline conditions, tipburn could be induced in both varieties by topical treatments with a Ca 2+ scavenger (EGTA) and Ca 2+ transport inhibitors (verapamil, LaCl 3) and reduced by supplying Ca 2+ along with a ionophore (A 23187). Tipburn symptoms were associated with locally produced ROS. O 2 - and oxidative damage significantly increased in leaf margins before symptom expression, while topical antioxidant applications (Tiron, DPI) reduced symptoms in treated leaves, but not in the rest of the plant. Antioxidant enzyme activity was higher in Po, and increased more in response to EGTA treatments, and may contribute to mitigating oxidative damage and tipburn expression in this variety.